2019
DOI: 10.15252/emmm.201809960
|View full text |Cite
|
Sign up to set email alerts
|

Non‐canonical cM et regulation by vimentin mediates Plk1 inhibitor–induced apoptosis

Abstract: To address the need for improved systemic therapy for non–small‐cell lung cancer ( NSCLC ), we previously demonstrated that mesenchymal NSCLC was sensitive to polo‐like kinase (Plk1) inhibitors, but the mechanisms of resistance in epithelial NSCLC remain unknown. Here, we show that cM et was differentially regulated in isogenic pairs of epithelial and mesenchymal cell lines. Plk1 inhibition inhibits cM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 73 publications
0
22
0
Order By: Relevance
“…Association of vimentin with signaling proteins has been shown to be regulated by vimentin phosphorylation and vimentin assembly state 48,49 . Shear stress did not significantly affect vimentin assembly state (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Association of vimentin with signaling proteins has been shown to be regulated by vimentin phosphorylation and vimentin assembly state 48,49 . Shear stress did not significantly affect vimentin assembly state (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The Plk1 inhibitor volasertib is a drug that induces apoptosis and also inhibits migration. Plk1 inhibition leads to a decrease in vimentin Ser82 phosphorylation and the corresponding loss of cMet phosphorylation via β1-integrin [118].…”
Section: Vimentin As a Drug Targetmentioning
confidence: 99%
“…This could also be shown in two erlotinib-resistant cell lines with activating EGFR mutations that harbored an EMT gene profile 49. Of note, it was recently shown that NSCLC cell lines (HEK293) with epithelial gene signature and constitutive cMET activation were highly resistant to volasertib treatment, whereas PLK1 inhibition prevented cMET phosphorylation in mesenchymal isogeneic cell pairs leading to high apoptosis rates.110 The combination of cMET and PLK1 inhibition in this setting led to sustainable xenograft tumor regression possibly paving the way for combination strategies involving PLK1 and cMET targeting therapy. Conclusively, acquired resistance to target therapies or conventional cytotoxic agents involving EMT might be a domain of PLK1 inhibition in the future.…”
Section: Preclinical Evidence For Emerging Biomarkersmentioning
confidence: 79%